Geoelectrical Investigations at Three Bridge Sites, North Nyala, Southern Darfour State, West-Sudan - E.A. Elzein Mohammed (Journal of Basic & Applied Sciences, 2021)
Resistivity measurements were carried out to delineate the depth of the basement rocks (bedrock) and the lithology of the overlying sediments for the purpose of bridges construction route. The survey was conducted at three sites: Andro, Duma and Manwashi, north Nyala, Southern Darfur State, Western Sudan. These sites (Andro, Duma and Manwashi ) are located along Nyala _ El-Fashir road at a distance approximately of 15km, 42km and 75km from Nyala (respectively). The surface geology of the area is dominated by the basement complex rocks which are overlain by thin layer of superficial deposits The modeling of the VES data was done using IX1D software. The final results of the modeled and interpreted resistivity data are presented in the form of geoelectrical sections. These sections have shown a close agreement with the geological and hydrogeological conditions of the area. Three zones were identified in these sections, they are the top dry zone (<1m to >3m) representing the superficial deposits, the middle zone (Saturated zone) represents the groundwater aquifer. It varies in lithology from weathered and cracked basement rocks to the Alluvial deposits with a significant heterogeneous nature which varies from clayey, silty, sandy, pebbly and boulders layers. The bottom zone (Fresh basement rocks) represents the bedrock. It indicate an increase of hardness and compaction from Andro , Duma and Manshawi sites respectively. These findings can be used successfully for constructions the bridges of the three sites.